Evidence supporting neuroprotective effect of adipose derived stem cells on PC12 cells against oxidative stress induced by H2O2 - Ghorabi, M. T.; Aliaghaei, A.; Sadeghi, Y.; Shaerzadeh, F.; Rad, A. A.; Mohamadi, R.; J. Ebrahimi, M. (Cellular and Molecular Biology, 2017)
Adipose-derived stem cells (ADSCs) are a population of cells derived from adipose tissue. ADSCs exhibit multilineage development potential and are able to secrete various factors, which influence adjacent cells. The present study examined the protective effect of ADSC's conditioned media (ADSC-CM) on PC12 cells exposed to H2O2, an oxidative injury model. After isolation, ADSCs were cultured and their osteogenic and adipogenic differentiation confirmed. Then, PC12 cells were co-treated with ADSC-CM and H2O2. Next, the effects of ADSC-CM on neurite outgrowth and cell differentiation in the presence of H2O2 were determined. Moreover, cell viability and apoptotic cell death percentage were evaluated using MTT assay, Hoechst staining and flow cytometry. Our results indicated the neuroprotective effects of ADSC-CM on morphological and morphometrical properties of neuron-like PC12 cells. Additionally, the profound decrease in percentage of apoptotic cells confirmed the protective effects of conditioned media from ADSCs that may be related to the release of trophic factors.